Widespread and Divergent Post‐Drought Loss of Gross Primary Production - Zhuoyi Zhao; Yanlian Zhou; Weimin Ju; Jingfeng Xiao; Xing Li (Geophysical Research Letters)
Abstract The impacts of droughts on the terrestrial ecosystem gross primary production (GPP) are evident with contemporaneous and lagged effects. However, the magnitude of post‐drought vegetation GPP loss remains unclear. This study quantitatively assessed the global post‐drought GPP loss during 2000–2022. The results showed that ∼23.89% of the drought‐induced GPP loss occurred after the drought, with a global mean of ∼0.74 Pg C yr−1. The higher proportions of post‐drought GPP loss were evident in humid regions, whereas the higher absolute post‐drought GPP loss mainly occurred in regions with higher vegetation cover. Furthermore, the global mean incidence and duration of post‐drought GPP loss were 50.66% ± 10.93% and 32.35 ± 10.56 days, respectively. The occurrence and persistence of post‐drought GPP loss exhibited a consistent correlation with aridity, but an inverse relationship with vegetation composition. These findings can contribute to a more accurate quantification of drought‐induced GPP loss, especially during the post‐drought period.